The Quality of Life Breast Cancer Patients Receiving Chemotherapy and The Factors Affecting It in a Regional Hospital in Gianyar - Yuliawati, Agustina Nila; Dewanti, Ni Putu Natasya; Ratnasari, Pande Made Desy (Universitas Muhammadiyah Surakarta, 2024)
The effects of breast cancer and chemotherapy can impact the quality of life (QOL) of patients. However, QOL can also be influenced by various characteristics directly related to them. This study aimed to analyze the QOL of breast cancer patients undergoing chemotherapy and the factors that can affect it. It was cross-sectional study conducted at a hospital in Gianyar, Bali in May-June 2024, with a sample of 135 breast cancer patients undergoing chemotherapy, selected using the purposive sampling method. The inclusion criteria required patients to have complete medical records and to agree to participate in the study, while those who did not fully complete the questionnaire were excluded. The research instrument used the EORTC QLQ C-30 and EORTC QLQ BR-23 questionnaires to assess QOL, as well as data collection sheets for personal and clinical information. Data were analyzed using Spearman's rho test, Eta test, and Mann-Whitney U-test, (CI 95%). Findings showed the majority of the respondents were <60 years old (84.4%), female (100.0%), had completed elementary school (46.7%), were employed (56.2%), lived far from health facilities (75.6%), had stage 2 cancer (48.1%), received treatment >3 times per month (51.9%), had no comorbidities (96.3%), underwent a combination of injection and oral chemotherapy (37.8%), and had an average QOL score of 93.2±8.9. Type of chemotherapy and comorbidities correlated with the QOL of the patients (p<0.001), while sociodemographic characteristics did not. Positive support from health workers, family, and the patient's environment was suspected to contribute to a good QOL.